Determinants of the World Investment Market Development in the Context of Global Transformations - Henryk DZWIGOL; Mariola DZWIGOL-BAROSZ (Communications of International Proceedings, 2020)
It is stated that investment is a factor of economic growth only if the financial system and real sector of economy interact closely, when financial flows of a cumulative, speculative, short-term nature gradually turn into long-term business investments. Financial markets development of the world countries and strengthening the role of in the global investment process has a complex nature and requires addressing many issues in the process of further economic transformations. Determining innovative direction of investment activity in the world countries is realized through the calculation of the relationship between the volumes of high-tech goods export and volumes of net portfolio investments at current prices for the period 2010-2016 in 130 countries.
Keywords: Economic Growth; Investment Market; Global Transformations; Net Portfolio Investments; Institutional Environment.